Estudio De La Brecha Empresario-Investigador. La Percepción Del Investigador - Méndez-Peón, Carlos Ángel; Herrera-Avilés, Margarita; Toriz-Palacios, Alfredo; González-Pérez, Manuel (European Scientific Journal, ESJ, 2016)
Technological innovation drives competitiveness and productivity of nations. The university-enterprise relationship (RUE) is determinant for the generation of an efficient innovation. The entrepreneur-researcher binomial (E-R) is the core process research and development (R & D) and technology transfer and knowledge (TTK). Despite efforts to improve RUE, little has been done to strengthen the relationship between E-R. This study confirms the existence of a gap between entrepreneur and researcher (ERG), it allows us to understand the importance of empathy in collaboration and identify factors affecting the relationship. The data were obtained by the exploratory and transversal approach, through interviews and questionnaires Likert. The sample consisted of expert researchers who have participated in joint innovation projects with entrepreneurs. The results indicate that 75% of researchers surveyed perceive the existence of an ERG under collaborative R & D and TTK. 78% of scientists see empathy as a significant variable for joint projects. The study revealed that only 16% of the factors affecting RUE influence the relationship of the binomial E-I significantly.